2012
DOI: 10.1007/s00404-012-2493-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cervical intraepithelial neoplasia (CIN) with colposcopic biopsy and efficacy of loop electrosurgical excision procedure (LEEP)

Abstract: Assessment of cervical lesions with colposcopic biopsy is an accurate method (concordance with cone histology 85.8%). Surgical treatment of high grade CIN with LEEP is a safe procedure with low recurrence rates, resulting in a clearance of cervical HPV infection in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 21 publications
7
58
1
7
Order By: Relevance
“…Those studies predominantly recorded whether there was a precise agreement between biopsy and conization results; they might have reported a higher correlation if overestimated results had been grouped together with precise agreement. The results of another German study were very similar to ours (85.8 %) with regard to histological agreement [10]. Baldauf et al also reported a very high agreement (89.6 %) between biopsy and conization results (overestimation 4.6%) [11].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Those studies predominantly recorded whether there was a precise agreement between biopsy and conization results; they might have reported a higher correlation if overestimated results had been grouped together with precise agreement. The results of another German study were very similar to ours (85.8 %) with regard to histological agreement [10]. Baldauf et al also reported a very high agreement (89.6 %) between biopsy and conization results (overestimation 4.6%) [11].…”
supporting
confidence: 86%
“…Studies have reported complete agreement in between 45 and 89.6 % of cases. Agreement within one histological grade was present in between 74 and 89.9 % of cases [5][6][7][8][9][10][11]. The crucial issue is to determine which conditions and factors can influence the accuracy of biopsy findings.…”
Section: Accuracy Of Colposcopically Guided Diagnostic Methods For Thmentioning
confidence: 99%
“…They concluded that CDB is an accurate method. The concordance rate was higher for CIN2/3 (95.1%) when compared with CIN1 (63.2%) (Duesing et al, 2012). We did not perform the excisional procedure (LEEP) for all of the CIN 1 cases; so concordance rate between CDB and LEEP was not evaluated statistically in our study.…”
Section: Discussionmentioning
confidence: 80%
“…In order to prevent abnormal cytology or CIN 3 recurrence, margin ablation is important, particularly in coin resection cases. Margin ablation is important in the prevention of recurrence after conization, and it is possible to reduce the follow-up visits after surgery in such cases (20,21).…”
Section: Cytological Findings After Treatment -----------------------mentioning
confidence: 99%